1988
DOI: 10.1227/00006123-198811000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Eosinophilia and Sterile Shunt Malfunction

Abstract: Cerebrospinal fluid (CSF) eosinophilia is a rare finding most often associated with central nervous system inflammatory processes, including parasitic, bacterial, and mycotic infections. It has also been seen as an allergic phenomenon. We present two cases of CSF eosinophilia occurring concurrently with sterile shunt malfunction. We speculate that CSF eosinophilia in our patients might have resulted from an allergic response to a foreign material such as suture, surgical glove powder, hair, cotton fibers, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This could be a reflection of a proinflammatory state which is only exacerbated by the trauma incurred with each ventricular catheter revision and has led some to advocate that ventricular catheter tracts associated with recurrent failures should, if anatomically possible, be abandoned in favor of virgin tracts (contralateral side, anterior vs. posterior approach). Repeated, short-interval, ventricular catheter obstruction should also raise suspicion for an allergic response, a diagnosis strongly supported by CSF eosinophilia in the context of sterile cultures [67, 68]. Although the PDMS catheter material is the most commonly implicated allergen [65, 69], some have even posited that the ethylene oxide used to sterilize many commercialized shunts may incite an immune response [70] .…”
Section: Obstructionmentioning
confidence: 99%
“…This could be a reflection of a proinflammatory state which is only exacerbated by the trauma incurred with each ventricular catheter revision and has led some to advocate that ventricular catheter tracts associated with recurrent failures should, if anatomically possible, be abandoned in favor of virgin tracts (contralateral side, anterior vs. posterior approach). Repeated, short-interval, ventricular catheter obstruction should also raise suspicion for an allergic response, a diagnosis strongly supported by CSF eosinophilia in the context of sterile cultures [67, 68]. Although the PDMS catheter material is the most commonly implicated allergen [65, 69], some have even posited that the ethylene oxide used to sterilize many commercialized shunts may incite an immune response [70] .…”
Section: Obstructionmentioning
confidence: 99%
“…In addition, they demonstrated CSF eosinophilia due to gentamicin administration according to a positive Prausnite-Kustner’s skin test which showed an immediate drug allergy to gentamicin. Traynelis et al [13]demonstrated the presence of discontinuous sheets of inflammatory cells, lipidized macrophages and multinucleated foreign-body giant cells upon microscopic examination following shunt tube removal. Tung et al [14]suggested that patients with CSF eosinophilia undergo shunt replacement more frequently than those without eosinophilia based on his study of 36 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilia in the CSF developed with medications, including the Ibuprofen, Ciprofloxacin, Trimethoprim-sulfamethoxazole, and intraventricular Vancomycin or Gentamicin (Patey et al, 1988), the Ibuprofen caused eosinophilic meningitis in a healthy girl (Bansal et al, 2014) and Isoniazid, anti-tuberculosis drug for two months as acute eosinophilic myocarditis (Zhang et al, 2015). Sterile CSF eosinophilia has also been noted after myelography with contrast agents and can accompany ventriculoperitoneal shunt implantation or malfunction (Traynelis et al, 1988). In one series of children with ventriculoperitoneal shunts, approximately one-third experienced a CSF eosinophilia of more than 8% in the absence of peripheral blood eosinophilia; these patients were more likely to experience shunt infections and require shunt revisions (Tung et al, 1991).…”
Section: Introductionmentioning
confidence: 99%